Inter-temporal stability of the International Stock Market Relationships: the case of Malaysian Stock Market in Relation to World's Major Stock Markets - Othman Yong, (Penerbit Universiti Kebangsaan Malaysia, 1990)
Most of the past studies regarding the co-movements of the international stock markets dealt with the potential gains to investors from international portfolio diversification. In general,these studies suggested that considerable gains were available to those investors willing to diversify internationally due to usually low positive or negative correlations between national stock markets (i.e., the unsystematic risk is reduced). Emphasis was not given to the possibility of using the movement in one market to predict the movement in another. This study, on the other hand, found that the information of the past movements in one market (referring to world's major markets) is not useful in predicting the movement in another market (referring to the Malaysian market) as shown by generally insignificant lagged correlations. Furthermore, inter-temporal instability of the correlations over time makes it difficult to select an efficient investment strategy due to a continuously changing efficient frontier.